Synthesis and Morphological Investigation of Flower-Like ZnO Nanostructures - Cătălin Mihăescu; Cristina Lavinia Nistor; Cristian Petcu; Raluca Ianchiş; Claudia Mihaela Ninciuleanu; Elvira Alexandrescu; Cristina Scomoroscenco; Ludmila Otilia Cinteză (Proceedings, 2020)
In recent years, ZnO nanostructures have attracted great interest due to their significant potential applications. [...]